Lincoln on leadership for today : Abraham Lincoln's approach to twenty-first-century issues - Phillips, Donald T. (Donald Thomas), 1952- (Houghton Mifflin Harcourt, 2017)
"Abraham Lincoln is recognized as one of history's finest leaders, a great president when the United States was under tremendous strain. But suppose he were alive today? How would Lincoln deal with today's high-pressure issues, from politics to business? Based on a lifelong study of Lincoln's life, writings, and speeches, best-selling author Donald T. Phillips offers compelling ideas on how Lincoln would employ his exemplary leadership and executive style. How would Lincoln handle today's frayed race relations, terrorism at home and abroad, gun control, and the influence of special interest groups on Congress? What would have been Lincoln's reaction to the invasion of Iraq? How would he have handled the Great Recession? What would be his stance on science and climate change? How did Lincoln feel about government entitlement programs? Would he have them at all? How would he feel about the growing gap between the haves and the have-nots, a worker's right to strike, the minimum wage, and labor unions? Would Lincoln have a mobile phone and embrace the whirl of social media? Phillips hews very closely to Lincoln's extensive writings and records to offer a fascinating look at how we might solve some of our most challenging problems, Lincoln-style,"--Amazon.com.